Conjunctival rotational flap versus autograf t techniques in pterygium surgery at AL-Hussain teaching hospital from 2009-2015 - mehdy, Dr.Imad salih (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
purpose :the aim is to compare the results of conjunctival flap and autograft in term of recurrence  rate  and  complications  in primary pterygium  surgeryMethods:Atotal of 70 patients (thirty male and forty female) operated for primary pterygium  with conjunctival autografts(in 36 eyes)or conjunctival flap (in 34  eyes) technique at AL-Hussain teaching  hospital-Kerbala  ,with 18 months follow up.Patients were asked for voluntary examinations of their  respective  ocular surface statusResults:Mean age was 43.5 years(range 21-70)42.65%  of the patients were male,70% of them worked  predominantly out doors.Mean  follow up  was 12months (3-18)Recurrence rate recorded was 8.3% graft,8.8% flap,however oedema was more in graft,granuloma was nil in bothConclusions:After this long follow up period for for conjunctival flap and autograft surgeries,there was no statistically significant differences in term of the recurrence rate,as well as autograft is alonger technique with more postoperative oedema